2020
DOI: 10.1155/2020/5324391
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of the Organochlorinated Herbicide Diuron by Rainforest Basidiomycetes

Abstract: The main organochlorinated compounds used on agricultural crops are often recalcitrant, affecting nontarget organisms and contaminating rivers or groundwater. Diuron (N-(3,4-dichlorophenyl)-N ′ ,N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Nonetheless, most reports of HCB biodegradation employed diluted concentrations of this pollutant (in the range of 0.08 ng g −1 to 50 μg g −1 ), as many microorganisms could not thrive in environments containing higher concentrations of organochlorines. 21,[41][42][43][44] Although the degradation of organochlorinated compounds by fungal laccases from basidiomycetes has been reported, 33,45,46 few research groups explored the degradation of HCB by basidiomycete fungi. In this sense, HCB degradation and its underlying metabolic pathways have been only explored mostly on bacterial models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, most reports of HCB biodegradation employed diluted concentrations of this pollutant (in the range of 0.08 ng g −1 to 50 μg g −1 ), as many microorganisms could not thrive in environments containing higher concentrations of organochlorines. 21,[41][42][43][44] Although the degradation of organochlorinated compounds by fungal laccases from basidiomycetes has been reported, 33,45,46 few research groups explored the degradation of HCB by basidiomycete fungi. In this sense, HCB degradation and its underlying metabolic pathways have been only explored mostly on bacterial models.…”
Section: Discussionmentioning
confidence: 99%
“…Although the degradation of organochlorinated compounds by fungal laccases from basidiomycetes has been reported, 33,45,46 few research groups explored the degradation of HCB by basidiomycete fungi. In this sense, HCB degradation and its underlying metabolic pathways have been only explored mostly on bacterial models 1,7,21,41–44,47,48 …”
Section: Discussionmentioning
confidence: 99%
“…They also confirmed that crude laccase extracts from the white-rot fungus Ganoderma lucidum could degrade. In contrast to Coelho-Moreira et al (2018) and Henn et al (2020)…”
Section: Functional Enzymes and Genes Involved In Diuron Degradationmentioning
confidence: 91%
“…They also confirmed that crude laccase extracts from the white-rot fungus Ganoderma lucidum could degrade. In contrast to Coelho-Moreira et al (2018) and Henn et al (2020) applied crude enzymatic extracts of Pycnoporus sanguineus but did not catalyze the degradation of DUR in vitro , despite the high degradation rate of P. sanguineus and the strong inductive effect of DUR on laccase synthesis and secretion. Hu et al (2020) observed that DUR concentrations remained constant after incubating T. versicolor laccase in in vitro experiments, despite substantial laccase activity.…”
Section: Functional Enzymes and Genes Involved In Diuron Degradationmentioning
confidence: 97%
“…There are different fungal strains that have been utilized in the degradation of diuron (Li et al, 2021), that is, Pycnoporus sanguineus MCA 16 (Henn et al, 2020), Pluteus cubensis SXS 320 (Henn et al, 2020), Trametes versicolor K-41 (Mori et al, 2018), respectively (Gangola et al, 2015). Bending et al (2002) investigated the ability of nine species of white rot fungus to degrade contrasting mono-aromatic pesticides.…”
Section: Herbicides Mycoremediationmentioning
confidence: 99%